Financial Performance Analysis of PT Astra Agro Estari and Company Value Estimation - Puspoyo, Ajianto; Sukarno, Subiakto (Journal of Business and Management, 2014)
Palm oil is the world’s most consumed and produced vegetable oil. Southeast Asia region supplies 89.97% of global Crude Palm Oil (CPO) demand, Indonesia is the world’s leader of CPO supplier that own about 53.7% global market. The CPO production and export is also became one of the most influencing commodity in Indonesian trading balance. The financial performance of PT Astra Agro Lestari as Indonesian leading palm oil company will be compared with the palm oil companies with the highest market capitalization in Southeast Asia region. The company valuation also performed to estimate the value of PT Astra Agro Lestari. The method that is used to perform those analyses is the financial ratios comparison with trend analysis, cross-section analysis, common size financial statement, DuPont analysis, and the compound annual growth rate comparison. Then, the valuation method used to value the company is the discounted cash flow (DCF) model, market approach, and asset-based approach. The result of this research, addressed to elevate the company performance of PT Astra Agro Lestari in order to improve the competitiveness in global palm oil competition. The overall financial performance of PT Astra Agro Lestari actually left behind Univanich Palm Oil regardless the business scale difference. PT Astra Agro Lestari continuously lost its business efficiency from 2009 to 2013. The result itself shows that PT Astra Agro Lestari would perform better in the future if the company looking back to export opportunity in increasing global CPO price in upcoming years. PT Astra Agro Lestari also should make its operational more efficient and increase the productivity to make the financial performance better. Two out of three company valuation methods indicates that the share price of PT Astra Agro Lestari is underpriced in the market, thus, PT Astra Agro Lestari shares are prospective in the future.Keywords: Financial performance comparison, Crude Palm Oil (CPO), financial ratios, DuPont analysis, company valuation, discounted cash flow valuation.